Effect of Nadi Shodhana Pranayama on Respiratory Parameters in School Students - Suba Malani S2, Shyamala Thirumeni1, Sivapriya D V1*, (Recent Research in Science and Technology, 2010)
Background: Yogic breathing techniques are very important for inducing relaxation. It is thought by many cultures that the process of breathing is the essence of being. The ultimate goal is to relax quickly and to improve the respiratory efficiency. It’s important for children to practice yogic breathing techniques on a daily basis. Breathing techniques help to change subtle energies within the body for health and well being. Modern human is the victim of stress and now a days yoga is widely used among adult population to relive stress but leastly concentrated in children inspite of its vast effects. Aim: Current study was undertaken to create awareness in the health benefits of pranayama and to inculcate yoga in school students so that they can gain a healthy life in future. Methods: This study was designed to evaluate the effects of a 45 days daily practice of Nadi Shodhana Pranayama yoga practice on peak expiratory flow rate (PEFR), forced vital capacity (FVC), forced expiatory volume in 1 sec (FEV1) and respiratory rate (RR) in school students of both sexes. 115 school students aged 8 – 14 years studying in Visa Nursery & primary school, Chennai were recruited for the study. Healthy student with no history of present and past illness were selected. The participants were trained to perform Nadi Shodhana Pranayama and the study was done for 45 days . The respiratory parameters PEFR, FVC, FEV1 & RR were measured before and after practice of Pranayama. Results: The results of this study showed significant increase in PEFR, FVC, FEV1. The RR declined after the practice of Nadi Shodhana Pranayama. Conclusion: The positive results found in the present study can be applied to all schools to improve the pulmonary functions of the students . A few minutes practice daily may help in setting the mind better on works and studies. The daily practice could maintain better physical and mental health to have a better future.